Dermatophytic blepharitis due to Microsporum gypseum. An adult variety of tinea faciei with dermatophytoma - Edoardo Torres - Guerrero; Laura Ramos - Betancourt; Erick Martínez - Herrera; Stefanie Arroyo - Camarena; Carlos Porras-López; Roberto Arenas (Our Dermatology Online, 2015)
Tinea faciei, is a facial superficial mycosis. The most frequent etiological agents are Microsporum canis, Trichophyton rubrum and T. tonsurans. We report a 40 year-old woman, with an eight days history of an erythematous plaque on her superior right eyelid. Hyphae and dermatophytoma were easily visualized in KOH examination, and Microsporum gypseum was isolated.